The effectiveness of visual input enhancement on the noticing and L2 development of the Spanish past tense - Loewen, Shawn; Inceoglu, Solène (Studies in Second Language Learning and Teaching, 2016)
Textual manipulation is a common pedagogic tool used to emphasize specific features of a second language (L2) text, thereby facilitating noticing and, ideally, second language development. Visual input enhancement has been used to investigate the effects of highlighting specific grammatical structures in a text. The current study uses a quasi-experimental design to determine the extent to which textual manipulation increase (a) learners’ perception of targeted forms and (b) their knowledge of the forms. Input enhancement was used to highlight the Spanish preterit and imperfect verb forms and an eye tracker measured the frequency and duration of participants’ fixation on the targeted items. In addition, pretests and posttests of the Spanish past tense provided information about participants’ knowledge of the targeted forms. Results indicate that learners were aware of the highlighted grammatical forms in the text; however, there was no difference in the amount of attention between the enhanced and unenhanced groups. In addition, both groups improved in their knowledge of the L2 forms; however, again, there was no differential improvement between the two groups.